Nanoinformatics 2018
DOI: 10.1007/978-981-10-7617-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Modulation of Functional Nanolayers

Abstract: Regions of a few nanometers at the surface or interface of a material exhibit various functional properties, which differ from those of the bulk because the electrons and/or ions receive different potentials due to the incoherent atomic arrangement. High-quality epitaxial films of functional materials called "nanolayers" are important to utilize such functional properties. However, fabrication of high-quality nanolayers of complex materials with complicated crystal structures is usually challenging due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Perovskites have provide very special class of materials with excellent optical and photoluminescence properties. Studying the optical properties of single domain crystals of BaTiO 3 at various temperatures (Ohta and Hiramatsu (2018)) showed that the refractive index of the crystal was nearly a constant value (2.4 from 20° to 90 °C & reached 2.46 at 120 °C) (Zhang et al, 2017). The single crystal of BaTiO 3 , 0.25 mm thick was found to transmit from 0.5 μ to 6 μ.…”
Section: Propertiesmentioning
confidence: 99%
“…Perovskites have provide very special class of materials with excellent optical and photoluminescence properties. Studying the optical properties of single domain crystals of BaTiO 3 at various temperatures (Ohta and Hiramatsu (2018)) showed that the refractive index of the crystal was nearly a constant value (2.4 from 20° to 90 °C & reached 2.46 at 120 °C) (Zhang et al, 2017). The single crystal of BaTiO 3 , 0.25 mm thick was found to transmit from 0.5 μ to 6 μ.…”
Section: Propertiesmentioning
confidence: 99%